Moyamoya Disease Update - Cho, Byung-Kyu.; Tominaga, Teiji; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2010)
Moyamoya disease (MMD) was first reported as a new entity among vascular disorders in 1957. Named for the abnormal vascular networks found around the occluded distal internal carotid artery, it is the most common pediatric cerebrovascular disease in East Asia. In recent years large amounts of data on MMD have been collected and important investigations have been carried out in Japan and Korea, even as the pathophysiology of the disease remains to be discovered. This monograph covers a diversity of topics and presents a systematic compilation of the data and current status of MMD in clinical practice and basic research. With contributions by more than 70 authors, the book includes sections on genetics, computational analysis of hemodynamic shear stress, new imaging techniques, and endovascular treatment of MMD, along with practical applications and future directions for gene and stem cell therapies. For neurosurgeons as well as neurologists and pediatricians, this volume will help lead to more efficient and informed management of MMD.
Overview -- Pathology of Moyamoya Disease -- Unilateral Moyamoya Disease -- Epidemiology -- Epidemiology of Moyamoya Disease -- Familial Moyamoya Disease -- Genetics -- Overview -- Genetic Linkage Study -- Single Nucleotide Polymorphism and Moyamoya Disease -- HLA Studies in Moyamoya Disease -- Pathophysiology I: Protein, Cell, and Immunology -- Proteins, Cells, and Immunity in the Moyamoya Disease: An Overview -- Vascular Smooth Muscle Cell-Related Molecules and Cells -- Ischemia/Angiogenesis-Related Molecules and Cells -- Immunological Aspects of Moyamoya Disease -- Pathophysiology II: Hemodynamics, Biomechanical Aspect -- Hemodynamics -- Regional Predilection of Lesions and Stages of Moyamoya Disease -- Clinical Features -- Clinical Features of Moyamoya Disease: An Overview -- Headache in Moyamoya Disease -- Involuntary Movement -- Progression of Moyamoya Disease -- Systemic Arterial Involvement in Moyamoya Disease -- Associated Neurosurgical Diseases -- Diagnostic Evaluation I: Morphological Imaging -- Overview of Image Diagnosis of Moyamoya Disease -- Preoperative and Postoperative MRA -- Diagnostic Evaluation: Morphological Imaging MRI -- Diagnostic Evaluation II: Functional Imaging -- Functional Neuroimagings (3z(BOverview(3y (B-- Brain Perfusion SPECT in Moyamoya Disease -- Iomazenil SPECT (BZP-Receptor) -- Perfusion Imaging in Moyamoya Disease -- Positron Emission Tomography in Moyamoya Disease -- Diagnostic Evaluation III: Electrophysiology -- Electroencephalography (EEG) in Moyamoya Disease -- Magnetoencephalography (MEG): Its Application to Moyamoya Disease -- Surgical Technique -- Overview -- Moyamoya Disease and Anesthesia in Children -- ACA Territory Reinforcement -- PCA Territory Reinforcement -- Endovascular Treatment of Moyamoya Disease -- Surgical Outcome -- Overview -- Risk Factors for Complication -- Cognition and Quality of Life -- Special Consideration I -- Overview: Issues in Young Children and Adults -- Moyamoya Disease in Young Children -- Moyamoya Disease in Adult: Management of Hemorrhage -- Moyamoya Disease in Adult: Post-Bypass Symptomatic Hyperperfusion -- Special Consideration II -- Moyamoya Syndrome: Pial Synangiosis -- Pregnancy and Delivery in Moyamoya Disease -- Asymptomatic Moyamoya Disease -- Hyperthyroidism in Moyamoya Disease -- Enhancer of Revascularization, Gene and Stem Cell Therapies -- Special Consideration III -- Moyamoya Disease in North America -- Moyamoya Angiopathy in Europe -- Moyamoya Disease in China -- Future Perspectives -- Future Perspectives in Moyamoya Disease.s
Keywords: Medicine; Neurosurgery; Medicine & Public Health; Neurosurgery